Epidemiology of traumatic myiasis due to Chrysomya bezziana in Indonesia - April Hari Wardhana; I. Abadi; M. M. Cameron; P. D. Ready; M. J.R. Hall (Indonesian Center for Animal Research and Development (ICARD), 2018)
Epidemiology of traumatic myiasis in Indonesia was studied by the widespread collection of fly larvae from infested livestock in passive case detection surveys involving veterinary clinics. In addition, monthly data from Kediri regency in Eastern Java were analysed from 2006-2009 to explore the seasonality of myiasis. Larvae from a total of 260 cases from the nationwide survey and 341 cases from Kediri were identified. Except for 5 cases of chicken infestation due to Musca species in the nationwide survey, all other cases were exclusively caused by the Old World screwworm (OWS) fly, Chrysomya bezziana (Diptera: Calliphoridae). The monthly numbers of cases at Kediri were very variable, with cases in all months, but there was statistical evidence for an increase in cases in January and December, during the rainy season. The greatest numbers of infestations recorded were from cattle and goats. The most frequently infested sites nationwide and in Kediri were the vulva and umbilicus, associated with calving, which is a major risk period for traumatic myiasis. Mitochondrial DNA typing of 176 specimens was useful for detecting multiple infestations, but no association was found between genetic lineage and host. The equatorial climate of Indonesia, combined with poor husbandry systems are factors that help to support OWS fly development year round. Even if not considered a disease of strategic importance, screwworm myiasis remains a threat to livestock production in Indonesia and a major welfare issue that requires constant interventions by farmers. The new and collated epidemiological data presented represent the most extensive survey of traumatic myiasis in Indonesia to date and provide a valuable baseline to support integrated pest management programs.